Metode Validasi Analisis Senyawa Kimia Obat dalam Sampel Biologis (Plasma Darah) - Gisel Rizuna Qothrunnada; Issabella Elsiana; Kholifatul Ulum; Klaritya Anisya Kurnia; Shafa Qotrunnada Widyatamaka; Shipa Paujiah; Fira Aulia Fatan (Syntax Corporation Indonesia, 2022)
Blood plasma is used as a biological sample in determining the levels of drug compounds because the concentration of the drug will bind to its receptors and determine the size of the pharmacological effect of a drug. The purpose of this study was to determine the accuracy of human blood plasma as a sample in several validation methods with different analytes. The research method used is by conducting a literature study in several credible journals with the criteria of the journals of the last 10 years regarding the determination of levels of drug compounds in human blood. The results obtained from five different analytes, namely glibenclamide combination with metformin, formalin, vancomycin, lisinopril and a-mangostin which have been validated using various validation methods, namely SPE-MIP followed by HPLC, UV-VIS spectrophotometer, HPLC-UV, UPLC and TLC densitometry using human blood plasma samples, all meet the validation requirements. So it can be concluded that, human blood plasma used as a sample in the validation test with various different methods and analytes that have been carried out is entirely accurate because all validation test methods meet the requirements